On Foreign Participation and Hiring Patterns After Privatization - Virgilio Galdo; Alberto Chong (Inter-American Development Bank, Research Department, 2006)
Critics of globalization claim that foreign ownership of privatized firms is linked to negative post-privatization labor outcomes, such as more firing and less hiring. This paper uses new firm-level data for a cross section of countries to test this idea and provides evidence that foreign purchasers of state-owned enterprises tend to acquire firms that were already better restructured before privatization. Additionally, this paper does not find evidence that foreign participation in privatized firms is linked to negative labor outcomes.
Keywords: 330; Privatisierung; Auslandsinvestition; Personalbeschaffung; Welt